Big five personality traits as predictors of systems thinking ability of upper secondary school students - Roslan, Samsilah; Hasan, Syaza; Zaremohzzabieh, Zeinab; Mohamad Arsad, Nurazidawati (Universiti Putra Malaysia, 2021)
Developing system thinking skills among secondary school students has been set as an educational goal for years. The emerging properties of a system have recently been influenced by the characteristics of each student. Thus, this study examines the Big Five personality traits as predictors of Malaysian school students‘ systems thinking. Quantitative data was obtained using a standardized questionnaire with established scales (the Goldberg’ International Personality Item Pool and the Systems Thinking Scale) from 196 upper secondary school students. The results indicate that personality traits affect secondary students‘ system thinking, and almost thirty percent of the variation in the Malaysian system thinking skill can be elucidated by its sub-domains. Although agreeableness has superior impacts on systems thinking, extraversion seems to have less importance on their systems thinking. The results also reveal the negative association between extraversion and neuroticism and systems thinking. We conclude that certain personality traits can improve systems thinking and promote students’ ability to solve complex problems. The implications of these findings for the enhancement of systems thinking among school students are discussed.